Nucleoside Phosphorylases - Lewkowicz, Elizabeth Sandra (2006)
Nucleoside phosphorylases (NPs) are transferases that catalyse the reversible cleavage of the glycosidic bond of ribo- or deoxyribo nucleosides, in the presence of inorganic phosphate, to generate the base and ribose- or deoxyribose- 1-phosphate. Since pyrimidine as well as purine nucleoside phosphorylases exist, the combination of both enzymes makes possible the generation of purine nucleosides from pyrimidine ones. As a consequence, NPs from different sources, mainly bacterial, have been exploited as tools for the enzymatic synthesis of nucleoside analogues. These molecules are extensively used as antiviral and anticancer agents because of their ability to act as reverse transcriptase inhibitors or chain terminators in RNA or DNA synthesis. This review covers literature reports from 2000 on, focused mainly on the synthesis of nucleosides by free and immobilised microbial whole cells, along with some examples of modified nucleosides obtained by coupling transglycosylation to other enzymatic reactions. The biological aspects of NPs are also discussed since they became an interesting target for clinical applications due to their key role in nucleotide metabolism. Finally, brief comments about their structures and catalytic mechanisms are included.